Layer-dependent ferroelectricity in 2H-stacked few-layer α-In2Se3. Issue 5 (5th March 2021) - Lv, Baohua; Yan, Zhi; Xue, Wuhong; Yang, Ruilong; Li, Jiayi; Ci, Wenjuan; Pang, Ruixue; Zhou, Peng; Liu, Gang; Liu, Zhongyuan; Zhu, Wenguang; Xu, Xiaohong
Abstract : Layer-dependent ferroelectric polarization in 2H-stacked α-In2 Se3 attributed to a 180 degree in-plane rotation in the adjacent layers is reported. Abstract : Atomically thin two-dimensional (2D) van der Waals materials have exhibited many exotic layer-dependent physical properties including electronic structure, magnetic order, etc. Here, we report a striking even–odd layer dependent oscillation in the ferroelectric polarization of 2H-stacked few-layer α-In2 Se3 nanoflakes. As characterized by piezoresponse force microscopy (PFM), when the in-plane (IP) electric polarization of 2H-stacked α-In2 Se3 films is electrically aligned, the out-of-plane (OOP) polarization of the odd-layer (OL) samples is obviously larger than that of the even-layer (EL) ones. Similarly, samples with electrically aligned OOP polarization also show even–odd layer dependent IP polarization. Such an even–odd oscillation, as confirmed by the density functional theory calculations, can be attributed to the strong intercorrelation of the IP and OOP electric polarization of the α-In2 Se3 monolayers and the special 2H-stacking structure of a 180 degree IP rotation with respect to the adjacent layers. Moreover, a negative differential resistance, interestingly, is induced by the polarization flip with a small coercive field of ∼1.625 kV cm −1, and its peak-to-valley ratio can be tuned up to ∼7 by the gate. This work demonstrates that the delicate stacking geometry of multilayer α-In2 Se3 can bring an interesting even–odd ferroelectric effect, enriching the layer-dependent physical properties of the 2D materials family.